Aging and the Life Course: an introduction to social Gerontology - Jill Quadagno (McGraw Hill Higher Education, 2005)
Berisi : Chapter Quizzes, Learning Styles Assessment, Internet Primer, Guide to Electronic Research, Study Skills Primer, Web Link, Help. Berupa teks dan link.